2021
DOI: 10.1016/j.micpath.2021.105189
|View full text |Cite
|
Sign up to set email alerts
|

An evidence of microalgal peptides to target spike protein of COVID-19: In silico approach

Abstract: The outbreak of the novel coronavirus (COVID-19) has affected millions of lives and it is one of the deadliest viruses ever known and the effort to find a cure for COVID-19 has been very high. The purpose of the study was to investigate the anti -COVID effect from the peptides derived from microalgae. The peptides from microalgae exhibit antimicrobial, anti-allergic, anti-hypersensitive, anti-tumor and immune-modulatory properties. In the In silico study, 13 cyanobacterial specific pepti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 29 publications
(32 reference statements)
0
8
0
Order By: Relevance
“…In general, microalgae are rich in various phytochemicals like carotenoids, phycocyanin, phenolics, amino acids, polyunsaturated fatty acids, and sulphated polysaccharides [4,5]. These compounds are providing excellent various biological actions including, antioxidant, antimicrobial, antiviral, antitumoral, antiinflammatory, and anti-allergy effects [6,7]. Some microalgae such as Chlorella vulgaris and Spirulina platensis have been used in several areas in nutraceutical, pharmaceutical, cosmetics, nutrition, and functional quality of foods [8].…”
Section: Introductionmentioning
confidence: 99%
“…In general, microalgae are rich in various phytochemicals like carotenoids, phycocyanin, phenolics, amino acids, polyunsaturated fatty acids, and sulphated polysaccharides [4,5]. These compounds are providing excellent various biological actions including, antioxidant, antimicrobial, antiviral, antitumoral, antiinflammatory, and anti-allergy effects [6,7]. Some microalgae such as Chlorella vulgaris and Spirulina platensis have been used in several areas in nutraceutical, pharmaceutical, cosmetics, nutrition, and functional quality of foods [8].…”
Section: Introductionmentioning
confidence: 99%
“…There have been continuous efforts to get a cure for COVID‐19. Recently, in silico approach was utilized to identify anti‐COVID peptides from the microalgae Spirulina maxima (MubarakAli et al, 2021). MubarakAli et al (2021) used existing literature and Discovery Studios Visualizer to identify and predict the structures of 13 cyanobacterial‐specific peptides.…”
Section: Recent Trends For the Efficient Production Of Target Bioacti...mentioning
confidence: 99%
“…Recently, in silico approach was utilized to identify anti‐COVID peptides from the microalgae Spirulina maxima (MubarakAli et al, 2021). MubarakAli et al (2021) used existing literature and Discovery Studios Visualizer to identify and predict the structures of 13 cyanobacterial‐specific peptides. Further, molecular docking led to an understanding of the inhibitory effects of the peptides on the spike protein of COVID‐19 (MubarakAli et al, 2021).…”
Section: Recent Trends For the Efficient Production Of Target Bioacti...mentioning
confidence: 99%
See 1 more Smart Citation
“…Mostly, sulfated polysaccharides, in particular, fucoidan and carrageenan, were investigated. However, it has recently been reported that the Spirulina (Ratha et al 2020 ) and Spirulina peptides (MubarakAli et al 2021 ) possess the inhibitory effect on COVID-19 by binding to the spike protein. Moreover, phlorotannins are promising antiviral compounds.…”
Section: Algae As a Source Of Anti-viral Bioactive Compoundsmentioning
confidence: 99%